2006
DOI: 10.1128/jvi.80.1.161-171.2006
|View full text |Cite
|
Sign up to set email alerts
|

VP2 Cleavage and the Leucine Ring at the Base of the Fivefold Cylinder Control pH-Dependent Externalization of both the VP1 N Terminus and the Genome of Minute Virus of Mice

Abstract: Cylindrical projections surrounding the fivefold-symmetry axes in minute virus of mice (MVM) harbor central pores that penetrate through the virion shell. In newly released DNA-containing particles, these pores contain residues 28 to 38 belonging to a single copy of VP2, disposed so that its extreme N-terminal domain projects outside the particle. Virions are metastable, initially sequestering internally the N termini of all copies of the minor capsid protein, VP1, that is essential for entry. This VP1 domain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
86
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(90 citation statements)
references
References 44 publications
4
86
0
Order By: Relevance
“…Proteolytic cleavage of the externalized N terminus converts VP2 into the amino-terminal-shortened VP3 (9,12,37,51,57), a maturation step that has been suggested to prime the virions of the genus Parvovirus for VP1u exposure during cellular trafficking (11). Such maturation cleavage does not occur in B19, possibly because VP1u is always external.…”
Section: Vol 82 2008 Structure Of Infectious Human Parvovirus B19 7309mentioning
confidence: 99%
“…Proteolytic cleavage of the externalized N terminus converts VP2 into the amino-terminal-shortened VP3 (9,12,37,51,57), a maturation step that has been suggested to prime the virions of the genus Parvovirus for VP1u exposure during cellular trafficking (11). Such maturation cleavage does not occur in B19, possibly because VP1u is always external.…”
Section: Vol 82 2008 Structure Of Infectious Human Parvovirus B19 7309mentioning
confidence: 99%
“…We have shown that a large portion of the MVMp virions is excluded from either LAMP2-or TLR9-containing vesicles in RAW cells, suggesting that a majority of MVMp traffics away from the TLR9 signaling endosomes in pDCs. In addition, the MVMp capsid is extremely stable, capable of withstanding severe environmental conditions, including low pH (7,16). Thus, it is possible that the capsids remain impenetrable within the endolysosome, thereby restricting genomic DNA access for TLR9.…”
mentioning
confidence: 99%
“…The protrusions surrounding the threefold axis create valley-like depressions between the two-and threefold axes, as observed in Aleutian mink disease virus and B19. The cylindrical channel at the fivefold axis of the parvovirus capsid, which is implicated in packaging of the parvovirus genome and the phospholipase activity of the VP1 unique region (4,16,17), is conserved.…”
mentioning
confidence: 99%